Detonation propagation characteristics for CH4-2H2-3O2 mixtures in a tube filled with orifice plates. (15th March 2019) - Sun, Xuxu; Li, Quan; Li, Changhai; Lu, Shouxiang
Abstract: In this study, the detonation propagation characteristics of stoichiometric CH4 -2H2 -3O2 mixture are investigated comprehensively in a round tube with an inner diameter of 90-mm and 6-m in length. Three different orifice plates with the blockage ratios (BR) of 0.7 and 0.8 including circular, triangular and square orifice, are considered for the first time to investigate the effect of obstacle geometries on the detonation evolution. Eight high-speed piezoelectric pressure transducers are mounted on the outer wall to obtain the detonation velocity while the smoked foil technique is adopted to record the detonation cellular patterns. The results indicate that well within the limit, the detonation can propagate at about the theoretical CJ velocity (VCJ ). Near the limit, the velocity deficit is sharply enhanced but the detonation still can propagate at about 0.6VCJ, which seems to be a universal phenomenon before the failure of the detonation. In the smooth tube, a sudden velocity drop and the single-headed spin can be seen near the critical condition, and the critical pressure (Pc ) is 3 kPa. In the tube filled with obstacles, the effect of obstacle geometries on the detonation transmission can be ignored approximately for the BR = 0.7 case, and the critical pressures are increased to 7, 7 and 10 kPa, respectively. In the case of BR = 0.8, the effect of the orifice plates structures on the detonation propagation becomes more significant. The square orifice has the most serious impact on the detonation transmission, followed by triangular ones and the round hole has the least impact. The critical pressures are sharply enhanced to 10, 12 and 18 kPa, respectively. Finally, the effective diameter (deff ) and the characteristic parameter (L) are introduced to analyze the critical condition of the detonation propagation. The critical condition can quantified as deff /λ > 1 and L/λ > 7 where λ is the detonation cell size. Highlights: Effect of obstacle geometries on the detonation propagation is investigated. Near the limit, the detonation velocity deficit is explored. The mechanisms of detonation propagation are described. Analysis of the critical condition of detonation propagation are performed.